Las habilidades blandas y su influencia en el desempeño laboral del personal del Centro de Salud tipo C del cantón Tosagua - Mendoza Conforme, Lixon Darwin (2024)
The purpose of this research was to analyze the soft skills of public servants at the Type C Health Center in Tosagua canton to determinate their influence on job performance. Soft skills are defined as a set of emotional character skills related to social activity and indispensable within job performance since it allows individuals to effectively relate to others, work collaboratively, resolve conflicts, and adapt to the constant changes of the professional environment. To comply with the objectives set in the research, three important phases were executed, which allowed obtaining real and truthful information about the staff's level in terms of developing their skills. Firstly, the state of the art was established through a rigorous bibliographic review, which determined a significant relationship between the study variables. After this, field instruments (interview and survey) were designed under the Servqual model and the Likert scale model, which allowed identifying the weaknesses that public servants have in terms of soft skills. Once the deficiencies found were described, improvement strategies were developed using the 5w+1h planning matrix with the purpose of encouraging employees to continuously develop soft skills in order to improve job performance within the institution. It is important to be clear about how indispensable it is to have public servants with soft skills to achieve institutional success.